Reminder Apps for Muslim Daily Sunnah Activity - Zainol, Ahmad Masry (Universiti Teknologi PETRONAS, 2019)
The usage of mobile application is somehow become important in our daily life. It can be used to regularly plan our activities, work as reminder. In certain applications, worked as an interaction medium, which allow the users to connect with families and friends. Thus it is really crucial that, Islamic activities also follow suit with the development of technologies, so that Muslim mobile application users can get the benefits out of it. The development of mobile applications for Muslim activities has rapidly increased day by day. However, despite many applications being develop, the specific mobile applications for sunnah activities is still scanted. Therefore, the development of Reminder Application for Sunnah Activities is to fill the gap to cover on the sunnah activities for Muslim. The application will have planning guidelines, daily reminder and authentic hadith for reference and better planning on doing the activities on daily basis.